Financial instruments to hedge commodity price risk for developing countries - Lu, Yinqiu; Neftci, Salih N. (IMF working paper, 2008)
Many developing economies are heavily exposed to commodity markets, leaving them vulnerable to the vagaries of international commodity prices. This paper examines the use of commodity options-including plain vanilla, risk reversal, and barrier options-to hedge such risk. It then proposes the use of a new structured product-a sovereign Eurobond with an embedded option on a specific commodity price. By extracting commodity price risk out of the bond, such an instrument insulates the bond default risk from commodity price movements, allowing it to be marketed at a lower credit spread. The product is also designed to help developing countries establish a credit derivatives market, which would in turn enhance the marketability and liquidity of sovereign bonds.